2019
DOI: 10.1186/s12978-019-0697-6
|View full text |Cite
|
Sign up to set email alerts
|

Husbands’ involvement in family planning use and its associated factors in pastoralist communities of Afar, Ethiopia

Abstract: BackgroundHusbands play an influential role in women’s access to health care, such as family planning services. However, there is little evidence of the level of husbands’ involvement in family planning services among pastoralist communities, who possess a distinct lifestyle. This study was aimed to assess husbands’ involvement in family planning use and factors associated in pastoralist communities of Afar, Ethiopia.MethodsCommunity-based cross-sectional survey was conducted among randomly selected 418 marrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 16 publications
5
41
1
1
Order By: Relevance
“…This study also revealed that among those who had ever attended a family planning clinic, the majority (54.61%) had attended once, which has similar findings to that in communities in Afar, Ethiopia where husbands' involvement in family planning was about 42.2% [35]. However, most of the respondents indicated family planning is important and are ready to recommend to friends.…”
Section: Discussionsupporting
confidence: 79%
“…This study also revealed that among those who had ever attended a family planning clinic, the majority (54.61%) had attended once, which has similar findings to that in communities in Afar, Ethiopia where husbands' involvement in family planning was about 42.2% [35]. However, most of the respondents indicated family planning is important and are ready to recommend to friends.…”
Section: Discussionsupporting
confidence: 79%
“…Regarding husbands' involvement, 40.1% (95% CI: 36.2-44.0) participants had good involvement in partners' reproductive rights. This nding was in line with studies conducted in Bangladesh (40%) [22], southern Ethiopia (Bale zone, 41.4%) [24], and Afar, Ethiopia ( 42.2%) [29]. This consistency might be related to the fact that there is a rising development intervention in many of these countries like community health promotion, awareness creation, and the development of social media access.…”
Section: Discussionsupporting
confidence: 88%
“…Available evidence indicated that maternal health outcomes in LIMCs are related to the inadequacy of husbands' knowledge and involvement related to reproductive rights, lack of reproductive education, and spousal discussions which are the main cause of violations in reproductive rights [22,24,25,26,27,28,29]. Likewise, major contributing factors related to male partners' involvement in partners' reproductive rights are accessibility and utilization experience of reproductive health services, lack of spousal discussions on reproductive health and transportation access, and time to reach a health institution [30,31,32].…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 27 But it is lower than from a study conducted in Gedeo town (36%), 28 and Afar (42.2%). 29 The variation may be due to demographic, socio-cultural variation of the study subjects. For example, participants in the study in Bodit were urban residents which may know the family planning use whereas this study includes both rural and urban residents.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a study done in Tigray, Bodit, Debre Markos, Gedio, and Afar. 20 , 26 , 28 , 29 Men who have good knowledge about family planning may more likely have know-how about how to use contraceptives and play roles in couple contraceptive use and continuation, due to this reason husband’s background knowledge of family planning affects their involvement in LAPCM use.…”
Section: Discussionmentioning
confidence: 99%